(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This interview present the trajectory of teacher, actor, playwright Otávio Cabral within the theater scene in Maceió, beginning with his initiation in 1964. The narrative detailed the impact of the Teatro Deodoro on his artistic formation and the influence of figures such as Linda Mascarenhas and Paschoal Carlos Magno. It also addressed his involvement in groups such as the University Theater of Alagoas (TUA) and the Theater Group for Education and Culture (GTEC), situating them within the context of resistance to the military dictatorship. Cabral discussed his transition from administrative work to teaching theater at UFAL, highlighting art as a tool for social transformation and his understanding of theater as an amateur practice driven by passion.